The Views of Patients and Partners Toward Patient-Delivered Partner Therapy for Chlamydia: A Systematic Review. Issue 12 (December 2020) - Layton, Elly; Vaisey, Alaina; Goller, Jane L.; Coombe, Jacqueline; Temple-Smith, Meredith; Hocking, Jane
Abstract : Background: The majority of research on patient-delivered partner therapy (PDPT) has focused on its impact on reinfections. This study aimed to systematically review the evidence regarding the acceptability of PDPT by patients and partners for chlamydia infection. Methods: Three electronic databases were searched in March 2019 using terms related to PDPT. Studies were included if they reported on patient or partner acceptance of PDPT for chlamydia and were conducted in high-income countries. Actual and perceived acceptabilities of PDPT were assessed. Results: Thirty-three studies were included: 24 quantitative, 3 qualitative, and 6 mixed methods. Most were clinic based. Quantitative data showed that participants' perceived willingness to give PDPT to their partner(s) ranged from 44.7% to 96.3% (median, 84%), and 24% to 71% (median, 65%) of people who offered PDPT for their partner(s) accepted it. Partners' perceived willingness to accept ranged from 42.7% to 67% (median, 62%), and actual acceptance ranged from 44.7% to 80% (median, 77%). Those in longer-term relationships were generally more likely to accept PDPT; however, beyond this, we identified few clear trends. Qualitative studies found that convenience of PDPT and assurance of partner treatment were benefits, whereas partners not seeing a health care professional was viewed as a downside. Packaging that appeared legitimate and coaching on delivering PDPT were facilitators. Conclusions: Because patients bear responsibility for the success of PDPT, this information is crucial in clinical settings. Acceptance, perceived and real, of PDPT was generally high. Patients are best placed to determine whether PDPT is appropriate for them, and it should be offered as an option. Abstract : A systematic review of patient and partner views toward patient-delivered partner therapy for treating chlamydia yielded mixed results in factors associated with acceptance and use.Supplemental digital content is available in the text.